Iris Yellow Spot Virus Prolongs the Adult Lifespan of Its Primary Vector, Onion Thrips (Thrips tabaci) (Thysanoptera: Thripidae). Issue 3 (25th May 2019) - Leach, Ashley; Fuchs, Marc; Harding, Riley; Nault, Brian A
Abstract: Iris yellow spot virus (IYSV) from the genus Tospovirus, family Peribunyaviridae, reduces yield in several crops, especially Allium spp. IYSV is primarily transmitted by onion thrips ( Thrips tabaci ), but little is known about how IYSV impacts the biology of its principal vector. In a controlled experiment, the effect of IYSV on the lifespan and fecundity of onion thrips was examined. Larvae were reared on IYSV-infected onions until pupation. Individual pupae were confined until adults eclosed, and the lifespan and total progeny produced per adult were monitored daily. Thrips were tested for the virus in reverse-transcriptase polymerase chain reaction using specific primers to confirm the presence of IYSV. Results indicated that 114 and 35 out of 149 eclosing adults tested positive (viruliferous) and negative (nonviruliferous) for IYSV, respectively. The viruliferous adults lived 1.1–6.1 d longer (average of 3.6 d) than nonviruliferous adults. Fecundity of viruliferous and nonviruliferous onion thrips was similar with 2.0 ± 0.1 and 2.3 ± 0.3 offspring produced per female per day, respectively. Fecundity for both viruliferous and nonviruliferous thrips also was significantly positively correlated with lifespan. These findings suggest that the longer lifespan of viruliferous onion thrips adults may allow this primary vector of IYSV to infect more plants, thereby exacerbating IYSV epidemics.